Implementation of the Information and Documentation Management Officer (PPID) Policy in Pohuwato Regency - Arief Rahmat Giasi; Rauf A. Hatu; Sri Yulianty Mozin (Journal of General Education and Humanities, 2026)
The Policy of the Public Information and Documentation Management Officer is designed to guarantee public access to information and strengthen transparency in local government administration. However, in practice, implementing this policy often reveals gaps between normative compliance and the operational performance of public information services. This article analyzes the implementation of the Public Information and Documentation Management Officer policy in Pohuwato Regency using the policy implementation model proposed by Van Meter and Van Horn. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and document analysis. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that, normatively, the local government has established relatively comprehensive regulations and operational standards for public information services. Nevertheless, policy implementation has not been comprehensive and remains largely limited to responding to public information requests via online channels. Unsustainable resource availability, weak organizational functions for implementation, the absence of structured, formal communication mechanisms, and external support that remains primarily normative have led the policy to operate partially and reactively. These findings confirm that the implementation of the Public Information and Documentation Management Officer policy in Pohuwato Regency remains dominated by administrative compliance, without adequate institutional and operational strengthening to develop a functional, sustainable public information service system.